Prosiding Seminar Nasional Pendidikan Agama Katolik dan Budi Pekerti Peningkatan Sikap Ketaqwaan dan Semangat Gotong Royong dengan Metode PBL Siswa Kelas IV SDN 05 Jelai Hulu Tahun Ajaran 2024/2025 - Hilarius Hadi Susilo; Andarweni Astuti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to determine the Improvement of Attitude of Piety and the Spirit of Mutual Cooperation with the PBL Method of Grade IV Students of SDN 05 Jelai Hulu according to Phase B. This study uses a classroom action research method that is carried out in two cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection stages. The results of the study during the two cycles showed a significant increase where in the first cycle the average score obtained by students when applying the PBL model was 70% and in the second cycle by 85%. This shows that if the PBL learning method is applied properly and consistently, it will improve student learning outcomes.